Is the Party Really Over? Parties, Partisanship and the Politics of Crime - Guiney, Thomas C. (The British journal of criminology, 2024)
Political parties occupy a contradictory position in the criminological literature: at once active participants in the political contestation of crime but virtually absent from contemporary debates concerning the relationship between crime and democratic theory. In this paper, I present a ‘rational reconstruction’ of party and partisanship as distinctive modes of political association that are vital to liberal democratic systems that take seriously (1) the value of political pluralism and (2) the limits of public reason to yield definitive answers to the crime question. Currently, political parties are failing to perform these mediating roles satisfactorily and I conclude that a stronger normative commitment to an ‘ethic of partisanship’ can help to revitalize our representative democracies and foster a better politics of crime.